An Empirical Analysis of the Factors Leading to IPO Underpricing in China: New Evidence from A-Share Market (2010-2019) - Yang, Liu (2020)
The study on the phenomenon of IPO underpricing in China is of great significance for understanding and reducing the high level of IPO underpricing, realizing effective market allocation and improving resource utilization. This paper focuses on the first public offerings of A-shares in Shanghai and Shenzhen stock markets and 2113 companies that issued new shares from January 2010 to December 2019 are the samples in this paper. The information disclosed by the company, operating conditions and industry characteristics are collected and then 14 influencing factors are screened out. In order to estimate the influences of specific factors on the magnitude of IPO underpricing, a multiple regression is investigated through STATA. The results indicate that factors such as 2018 IPO system reform, firm age, tradable shares ratio, P/E ratio, P/B ratio, turnover rate and offering price are highly associated with IPO underpricing. While the remaining 7 variables (industry, geographic location, offering size, time gap, lot winning rate, total agency cost, asset-liability rate) have no impacts on the IPO underpricing problem.